Prevalence of tumours of the maxillomandibular complex diagnosed in a reference center in Brazil - Alessandra Laís Pinho Valente Pires; Izana Santos Borges Nascimento; Ana Letícia Marques de Souza Assis; Sheinaz Farias Hassam; Jener Gonçalves de Farias (Universidade Estadual de Campinas, 2021)
Tumors of the maxillomandibular complex are a heterogeneous group of lesions with a wide spectrum of clinical and histopathological characteristics. Aim: To evaluate the prevalence of odontogenic and non-odontogenic tumors associated with maxillary bones in a Reference Center for Oral Lesions. Methods: A cross-sectional study based on the medical records of a Reference Center for Oral Lesions at the State University of Feira de Santana, from 2006 to 2018. The data was initially analyzed in a descriptive manner. For bivariate analysis, Pearson's chi-square test was applied. The level of significance was set at 5%, where p≤ 0.05 is considered significant. Results: The prevalence of tumors was 2.27%. The average age of the individuals was 22.2 (± 15.1) years, the majority being up to 39 years (79.59%) and female (69.40%). A statistically significant difference was observed in relation to age (p = 0.00), as well as regarding the location of tumors in the anterior or posterior region (p = 0.02). Odontogenic tumors were benign, with odontoma being most frequent (46.90%), followed by ameloblastoma (16.30%). As for the non-odontogenic, neurofibroma (4.10%) and osteoma (4.10%) were the most common across the benign, while osteosarcoma accounted for 6.10% of cases. Conclusion: Odontogenic tumors were the most frequent in women, with age up to 39 years, odontoma being most common in the posterior region of the mandible. Among nonodontogenic tumors, central neurofibroma and osteoma were the most common. Osteosarcoma was more frequent in men over 40 years old and in the mandible region.